A label-free turn ON–OFF chemiluminescence strategy for lysozyme detection by target-triggered Cu2−xSe aggregation. Issue 34 (16th August 2019) - Zou, Hong Yan; Zhang, Fang Fang; Guo, Qing Juan; Yang, Tong; Huang, Cheng Zhi
Abstract : A label-free and sensitive turn on-off CL probe for Lys by modulating the biocatalytic ability of the Cu2− x Se was developed. The good catalytic ability of Cu2− x Se were suppressed for the aggregation when Lys was added, inducing the CL signal off. Abstract : The sensitive and rapid quantification of lysozymes (Lys) is a critical goal in clinical practice. Herein, a novel, label-free and sensitive turn ON–OFF chemiluminescent (CL) probe for Lys was developed based on modulating the biocatalytic ability of the Cu2− x Se nanoparticles. The synthesized Cu2− x Se nanoparticles could significantly enhance the chemiluminescence signal of the luminol–H2 O2 system owing to their high copper deficiency, where a very bright blue CL emission was directly observed by the naked eye in darkness and it could last for a long period of up to 36 minutes. However, Lys could induce the aggregation of the Cu2− x Se nanoparticles due to the electrostatic attraction, which could be monitored by SEM and dark-field imaging. The aggregated Cu2− x Se nanoparticles with lower copper deficiency density could suppress their catalytic ability and turn off the chemiluminescence of luminol–H2 O2 . The established ON–OFF CL strategy exhibited a selective response to protein Lys and showed a quantitative relationship between the changes in the CL signals and the concentration of Lys over a wide range of 0.5–5000 ng mL −1, with a low detection limit of 0.36 ng mL −1 . This study provides a promising strategy for detecting biomolecules by exploiting their specific interactions with nanomaterials.